2019
DOI: 10.5194/acp-19-11803-2019
|View full text |Cite
|
Sign up to set email alerts
|

Convective hydration in the tropical tropopause layer during the StratoClim aircraft campaign: pathway of an observed hydration patch

Abstract: Abstract. The source and pathway of the hydration patch in the TTL (tropical tropopause layer) that was measured during the Stratospheric and upper tropospheric processes for better climate predictions (StratoClim) field campaign during the Asian summer monsoon in 2017 and its connection to convective overshoots are investigated. During flight no. 7, two remarkable layers are measured in the TTL, namely (1) the moist layer (ML) with a water vapour content of 4.8–5.7 ppmv in altitudes of 18–19 km in the lower s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 48 publications
3
48
0
Order By: Relevance
“…The molecular weight (136.2 g mol −1 ) and density (1260 kg m −3 ) of α-pinene SOA were kept constant throughout the study. A number of studies have aimed to quantify the effect of aerosol viscosity on equilibration timescales through αpinene SOA by estimating coefficients of water diffusion (Renbaum-Wolff et al, 2013;Price et al, 2015;Lienhard et al, 2015). The water diffusion coefficients for α-pinene SOA from Lienhard et al (2015) were specifically used in this study because the parameterisation is valid down to the low temperatures observed high in the troposphere and covers the large temperature range appropriate for our experiment as indicated by the initial conditions in Table 1.…”
Section: Initial Conditionsmentioning
confidence: 99%
See 4 more Smart Citations
“…The molecular weight (136.2 g mol −1 ) and density (1260 kg m −3 ) of α-pinene SOA were kept constant throughout the study. A number of studies have aimed to quantify the effect of aerosol viscosity on equilibration timescales through αpinene SOA by estimating coefficients of water diffusion (Renbaum-Wolff et al, 2013;Price et al, 2015;Lienhard et al, 2015). The water diffusion coefficients for α-pinene SOA from Lienhard et al (2015) were specifically used in this study because the parameterisation is valid down to the low temperatures observed high in the troposphere and covers the large temperature range appropriate for our experiment as indicated by the initial conditions in Table 1.…”
Section: Initial Conditionsmentioning
confidence: 99%
“…A number of studies have aimed to quantify the effect of aerosol viscosity on equilibration timescales through αpinene SOA by estimating coefficients of water diffusion (Renbaum-Wolff et al, 2013;Price et al, 2015;Lienhard et al, 2015). The water diffusion coefficients for α-pinene SOA from Lienhard et al (2015) were specifically used in this study because the parameterisation is valid down to the low temperatures observed high in the troposphere and covers the large temperature range appropriate for our experiment as indicated by the initial conditions in Table 1. Figure 3 shows the diffusion coefficient as a function of temperature and water activity; highlighting how temperature conditions for homogeneous freezing, shown by the grey shaded region, interact with the published α-pinene SOA diffusion coefficients.…”
Section: Initial Conditionsmentioning
confidence: 99%
See 3 more Smart Citations